Economics and Constraints in the Operation of Biogas Technology - Pathania, M S (Annals of Arid Zone, 2016)
Beneficiaries of biogas plant does not use the dung cakes as fuel and hence result in reduction of use of traditional fuels. Saved dung can be used as FYM to increase the soil fertility. The amount of gas production is higher in summer as compared to rainy and winter seasons. The constraints should be removed by training the biogas plant owners.